Radiology In Infectious Diseases: Role In Diagnosis And Monitoring Of Infectious Conditions (Journal of Namibian Studies : History Politics Culture, 2022)
Radiological imaging is indispensable in the diagnosis and management of infectious diseases, offering critical insights into pathological processes and treatment outcomes. This article examines the pivotal role of radiology in infectious diseases, encompassing various imaging modalities and their applications.